Applications of Ultraviolet and Sub-ultraviolet Dermatoscopy in Neoplastic and Non-neoplastic Dermatoses: A Systematic Review - Paweł Pietkiewicz; Cristian Navarrete-Dechent; Yaei Togawa; Piotr Szlązak; Natalia Salwowska; Ashfaq A. Marghoob; Agnieszka Leszczyńska-Pietkiewicz; Enzo Errichetti (Dermatology and Therapy, 2024)
Abstract Dermatoscopy is a non-invasive and cost-efficient imaging technique augmenting clinical examination in neoplastic and non-neoplastic dermatoses. Recently, novel dermatoscopic techniques based on principles of reflectance/absorption and excited fluorescence have been developed. However, comprehensive data on their applications are sparse, and terminology is inconsistent. In this systematic review, we addressed the principles of ultraviolet (UV) imaging and proposed categorization based on spectral characteristics and signal acquisition, as well as discussed documented and potential clinical applications, safety measures during examination, and limitations associated with reflectance and fluorescence dermatoscopy. A literature search was conducted in the PubMed medical database until 2 December 2023 according to PRISMA guidelines, and 28 papers fit the scope of this review, whereas additional relevant articles were included to provide broader context regarding the chosen terminology, chromophores described, safety of sub-UV/UV, and regulations for light-emitting devices. UV and sub-UV dermatoscopy, categorized into different methods on the basis of the emitted wavelength and signal acquisition process (reflectance versus fluorescence), augment conventional dermatoscopy by optimizing safety margins in melanoma, facilitating early detection of tumor recurrence, and enhancing visualization in non-neoplastic conditions, including pigmentation disorders, intertrigo, papulo-desquamative dermatoses, and beyond. The review highlights the limitations of these techniques, including difficulty in differentiating melanin from hemoglobin, challenges in evaluating uneven surfaces, and artifacts. Although UV dermatoscopy complements conventional dermatoscopy, clinicians should be aware of their peculiarities, artifacts, limitations, and safety concerns to optimize their diagnostic accuracy and ensure patient’s safety.